Effects of Maternal Socioeconomic, Psychological, Nutritional Factor, and Ambient Smoke Exposure, on the Risk of Low Birth Weight: A Multilevel Evidence from Gunungkidul, Yogyakarta - Isne Susanti; Harsono Salimo; Yulia Lanti Retno Dewi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Low birth weight (lbw) is one of the main causes of infant mortality. Globally, 2.5 million infants die in the first month after birth, and about 1 million die in the first day of birth. This study aimed to determine the biopsycho